Contestations over space: Urban greening and displacement in Pumwani-Majengo, Nairobi - Opanga, Valentine; Guma, Prince (ERDKUNDE, 2025)
This paper examines the intersection of urban land appropriation with greening and ungreening in informal settlements, focusing on how internal power struggles drive displacement and exacerbate inequality. Using Nairobi’s Pumwani–Majengo as a case study, the research applies the Situated Urban Political Ecology (SUPE) framework, grounded in environmental justice, to analyse disputes over green spaces. Fieldwork combined semi-structured interviews, focus group discussions, life histories, field observations, and archival review with GIS and Landsat-based spatial analysis. Adaptive sampling, reflexivity, and methodological triangulation were used to navigate sensitive contexts and ensure data robustness. Displacement extends beyond physical relocation, severing social, cultural, and economic ties that are vital to resilience. Residents respond through resignation, negotiation, or active resistance. ‘Greening’ and ‘ungreening’ occur simultaneously, politicised and tied to dispossession, enclosure, and green ‘evictions’ that disproportionately affect vulnerable groups, particularly in riparian areas. Land changes create socioeconomic enclaves, privileging wealthier newcomers and marginalising low-income residents. The study challenges the notion of urban green spaces as neutral public goods, showing their appropriation for elite interests, and contributes to debates on environmental governance and land commodification in informal contexts by illustrating how green space disputes reproduce socio-spatial inequalities in rapidly growing cities.